2021
DOI: 10.1007/s00704-021-03582-4
|View full text |Cite
|
Sign up to set email alerts
|

Ranking of gridded precipitation datasets by merging compromise programming and global performance index: a case study of the Amu Darya basin

Abstract: Accurate representation of precipitation over time and space is vital for hydro-climatic studies.Appropriate selection of gridded precipitation data (GPD) is important for regions where longterm in-situ records are unavailable and gauging stations are sparse. This study was an attempt to identify the best GPD for the data-poor Amu Darya River basin, a major source of freshwater in Central Asia. The performance of seven GPDs and 55 precipitation gauge locations was assessed.A novel algorithm, based on the integ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 72 publications
0
9
0
Order By: Relevance
“…The CHIRPS dataset has been utilized for drought monitoring in recent years, with positive results in a variety of countries and areas (Habitou et al, 2020;Pandey et al, 2021). Globally there are some other studies (Salehie et al, 2021) has contributed in analyzing the precipitation extremes and its variations in other countries. Some of these studies has used CHIRPS datasets.…”
Section: Introductionmentioning
confidence: 99%
“…The CHIRPS dataset has been utilized for drought monitoring in recent years, with positive results in a variety of countries and areas (Habitou et al, 2020;Pandey et al, 2021). Globally there are some other studies (Salehie et al, 2021) has contributed in analyzing the precipitation extremes and its variations in other countries. Some of these studies has used CHIRPS datasets.…”
Section: Introductionmentioning
confidence: 99%
“…This dataset is available with a spatial resolution of 0.5 ×0.5 from 1979 to present at https://psl.noaa.gov/data/gridded/. Salehie et al (2021) assessed the ability of seven gridded precipitation datasets against 55 stations data over the Amu Darya basin. They found that CPC is the best dataset that capable of replicating the observed precipitation.…”
Section: Gridded Datamentioning
confidence: 99%
“…This dataset can be obtained with a resolution of 0.5⁰×0.5⁰ from https://psl.noaa.gov/data/gridded/. Salehie et al (2021a) assessed the ability of seven gridded Pr datasets' ability to estimate precipitation at 55 stations across the Amu Darya basin. They showed CPC as the best in replicating the observed Pr.…”
Section: Datasetsmentioning
confidence: 99%